2022
DOI: 10.1155/2022/9462139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Prenatal Ultrasound Score of the Placenta Combined with Magnetic Resonance Imaging in Diagnosis of Placenta Accreta during the Second and Third Trimester of Pregnancy

Abstract: Objective. The aim is to explore the clinical utility of the prenatal ultrasound score of the placenta combined with magnetic resonance imaging (MRI) in diagnosis of placenta accreta during the second and third trimester of pregnancy. Materials and Methods. A total of 108 pregnant women with suspected placenta accreta treated in Wuhan Hankou Hospital and Yantaishan Hospital of Yantai from January 2019 to January 2022 were retrospectively analyzed, the enrolled pregnant women received MRI examination because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This shows that ultrasound examination can determine whether PA occurs in patients using relevant imaging features, which is consistent with the findings of this study. However, conventional ultrasound examination is easily affected by subjective factors and clinical experience, and the ultrasound scoring system can compensate for its shortcomings [12,13] Chen et al [17] explored the evaluation value of the ultrasound scoring system in the treatment of PA disease; according to different USSs, patients with PA were divided into low, medium, and high groups, and the results showed that the risk of bleeding increased with an increase in USS, indicating that the ultrasound scoring system has high application value in the diagnosis and treatment of PA. Zhang et al [14] Table 2 Comparison of baseline data between 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that ultrasound examination can determine whether PA occurs in patients using relevant imaging features, which is consistent with the findings of this study. However, conventional ultrasound examination is easily affected by subjective factors and clinical experience, and the ultrasound scoring system can compensate for its shortcomings [12,13] Chen et al [17] explored the evaluation value of the ultrasound scoring system in the treatment of PA disease; according to different USSs, patients with PA were divided into low, medium, and high groups, and the results showed that the risk of bleeding increased with an increase in USS, indicating that the ultrasound scoring system has high application value in the diagnosis and treatment of PA. Zhang et al [14] Table 2 Comparison of baseline data between 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that ultrasound examination can determine whether PA occurs in patients using relevant imaging features, which is consistent with the findings of this study. However, conventional ultrasound examination is easily affected by subjective factors and clinical experience, and the ultrasound scoring system can compensate for its shortcomings [ 12 , 13 ] Chen et al [ 17 ] explored the evaluation value of the ultrasound scoring system in the treatment of PA disease; according to different USSs, patients with PA were divided into low, medium, and high groups, and the results showed that the risk of bleeding increased with an increase in USS, indicating that the ultrasound scoring system has high application value in the diagnosis and treatment of PA. Zhang et al [ 14 ] discussed the application value of prenatal placental USS in PA in the second and third trimesters of pregnancy, and the results showed that the USSs of patients with PA were significantly higher than those of patients without PA; the negative predictive value, positive predictive value, specificity, sensitivity, and accuracy of disease diagnosis can be significantly improved by combining MRI with USS. The results of this study also showed that the sensitivity and accuracy of combined diagnosis were significantly higher than those of conventional ultrasound examination and slightly higher than the evaluation of USS, but there was no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation